2017
DOI: 10.1111/cea.13025
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the MASK‐rhinitis visual analogue scale on smartphone screens to assess allergic rhinitis control

Abstract: The MASK-rhinitis VAS is a reliable and valid tool to assess allergic control on smartphone screens, at the population level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 24 publications
3
72
0
3
Order By: Relevance
“…In a previous study, it was found that the correlation between VAS global measured and VAS nose increased from ρ = .76 for day 1 to ρ = .83 for all days . Moreover, this was also confirmed in the validation study …”
Section: Methodssupporting
confidence: 70%
See 1 more Smart Citation
“…In a previous study, it was found that the correlation between VAS global measured and VAS nose increased from ρ = .76 for day 1 to ρ = .83 for all days . Moreover, this was also confirmed in the validation study …”
Section: Methodssupporting
confidence: 70%
“…A mobile phone app ( Allergy Diary ) central to MASK is available in 22 countries. It has been validated and was found to be an easy and effective method of assessing symptoms of AR using visual analogue scales (VAS) and work productivity …”
Section: Introductionmentioning
confidence: 99%
“…The ARIA guideline proposes a classification of AR based on symptom control, QOL, and daily impact as well as duration . Disease control associated with several health outcomes, including QOL and some mHealth end points, should be considered in ICPs. Although the duration of rhinitis is an important indicator of asthma multimorbidity, and duration and efficacy of treatment in AR, AR control should be considered as the most important end point for the pharmacist.…”
Section: Management Of Allergic Rhinitis In the Pharmacy: Aria‐pharmamentioning
confidence: 99%
“…VAS can be used to assess overall AR control (VAS global measure) as it relates to nasal symptoms and eye symptoms (Figures ,6). There is a high degree of correlation between VAS global measured (“Overall how much are your allergic symptoms bothering you today?”) and VAS for nose symptoms . An electronic form of the VAS exists in the Allergy Diary and has been validated against several end points.…”
Section: Management Of Allergic Rhinitis In the Pharmacy: Aria‐pharmamentioning
confidence: 99%
See 1 more Smart Citation